Isolation of Flavonoids and a Triterpene Ester with Potential Bioactivity from Ludwigia octovalvis (Jacq.) P.H. Raven (Onagraceae) Leaves - Sultana, Tamanna; Ashrafi, Sania; Das, Susmita; Hossain, Md Sakhawat; Ahsan, Monira; Azam, A T M Zafrul (Dhaka University Journal of Pharmaceutical Sciences, 2024)
Leaves of Ludwigia octovalvis (Jacq.) P.H. Raven (Onagraceae), a plant with a history of traditional medicinal use, were investigated to determine their bioactive constituents. Five known compounds were isolated and structurally characterized using extensive NMR spectroscopic techniques (¹H NMR, ¹³C NMR, COSY, HSQC, and HMBC) and comparison with literature data. These compounds included 7,4'-dihydroxy-5,6,8-trimethoxyflavone (1), 6,7,4'-trihydroxy-3,5-dimethoxyflavone (2), 4-hydroxybenzaldehyde (3), palmitic acid (4), and 6,27-(2-ethyl)- dihydroxy-3-oxo-olean-12-enyl palmitate (5). Bioactivity assays were performed on various fractions derived from crude methanolic (MeOH) extract of L. octovalvis. The hexane (LOH) and ethyl acetate (LOEA) fractions displayed significant DPPH free radical scavenging activity, with IC₅₀ values of 17.69 and 20.06 μg/mL, respectively, compared to the standard reference compound, ascorbic acid (5.96 μg/mL). The chloroform fraction (LOC) and LOH exhibited the most potent inhibition in the brine shrimp lethality bioassay (LC₅₀ = 0.037 and 0.012 μg/mL, respectively) compared to the standard, vincristine sulphate (0.45 μg/mL). The LOEA fraction demonstrated promising thrombolytic activity (43.34% clot lysis) compared to the standard, streptokinase (65.15%). Dhaka Univ. J. Pharm. Sci. 23(2): 171-179, 2024 (December)